P 12 Expansion of regulatory T cells by early CD28 Superagonist treatment attenuates neurodegeneration in MPTP mice. (May 2022) - Knorr, S.; Baumann, C.; Rauschenberger, L.; Beyersdorf, N.; Volkmann, J.; Ip, C.W.
Abstract : Introduction: The neuropathology induced by injection of the neurotoxin 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine (MPTP) is a commonly used and well characterized animal model of Parkinson's disease (PD). It shows pathophysiological hallmarks of PD such as the loss of dopaminergic neurons from the substantia nigra (SN) as well as neuroinflammation. Expansion of CD4 + Foxp3 + regulatory T cells (Tregs) by administration of a single dose of a CD28 Superagonist monoclonal antibody (CD28-SA) in the MPTP mouse model was evaluated as a potential anti-inflammatory therapy for PD. Materials and Methods: An acute PD-like disease was induced in mice by a regimen of four intraperitoneal injections at 2 h intervals of MPTP-HCl (20 mg MPTP/kg bodyweight in NaCl). The same injection intervals were used for saline injected control animals (ctrl). The CD28-SA (clone D665, in PBS) or vehicle (PBS) was subcutaneously injected at an early (three days before MPTP intoxication) or late time point (30 minutes after the last MPTP injection). The total number of Nissl + neurons and dopaminergic neurons (TH + ) of the SN were analysed by unbiased stereology seven days after MPTP intoxication. Two groups (MPTP + vehicle; MPTP + CD28-SA) were compared for the early treatment time point and four groups (ctrl + vehicle; ctrl + CD28-SA; MPTP + vehicle; MPTP + CD28-SA) for the late treatment time point. Results: At the late treatment time point significantly decreased total cell numbers of TH + and Nissl + neurons were observed in MPTP mice treated with vehicle compared to ctrl + vehicle and ctrl + CD28-SA mice (TH + neurons: ctrl + vehicle: 7840 ± 405; ctrl + CD28-SA: 8422 ± 286; MPTP + vehicle: 5289 ± 230 / Nissl + neurons: ctrl + vehicle: 18949 ± 309; ctrl + CD28-SA: 19490 ± 212; MPTP + vehicle: 14921 ± 783). CD28-SA treatment of MPTP mice did not rescue TH + and Nissl + neurons within the SN (TH + neurons: MPTP + D665: 5933 ± 462 / Nissl + neurons: MPTP + CD28-SA: 15523 ± 754). In contrast, early treatment of MPTP mice with the CD28-SA led to higher numbers of both TH + and Nissl + neurons compared to vehicle injected mice (TH + neurons: MPTP + CD28-SA: 5645 ± 313; MPTP + vehicle: 4912 ± 171 / Nissl + neurons: MPTP + CD28-SA: 13171 ± 574; MPTP + vehicle: 11062 ± 497). Discussion/Conclusion: Our delayed-start design study demonstrates a neuroprotective effect of early CD28-SA-induced CD4 + Foxp3 + Treg expansion within the SN in the MPTP mouse model of PD.